Association between glucose-to-lymphocyte ratio and mortality in patients with heart failure from the MIMIC-IV database: a retrospective cohort study - Gang Wu; Huanya Ke; Zijia Tong; Jie Yang; Juan Yang; Zhengjun Shen (Scientific Reports)
Abstract The glucose-to-lymphocyte ratio (GLR) has been associated with prognosis in various inflammatory diseases. However, its relationship with mortality among critically ill patients with heart failure admitted to the intensive care unit (ICU) remains poorly understood. This study aims to assess the association between GLR levels and mortality in this population and to evaluate the prognostic predictive value of GLR. This retrospective cohort study utilized data from the Medical Information Mart for Intensive Care IV (MIMIC-IV3.0) database, encompassing heart failure patients admitted between 2008 and 2022. The GLR was calculated as fasting glucose (mg/dL) divided by absolute lymphocyte count (K/µL). To evaluate the association between GLR levels and 30-day and 365-day mortality risk in heart failure patients, we employed RCS analysis, multivariable Cox regression, K-M survival curves, subgroup analyses, and ROC curves. These methods were used to assess both the prognostic relationship and the predictive accuracy of GLR. This study included a total of 14,417 patients. The association between GLR levels and all-cause mortality was found to be non-linear. In our analysis, GLR was found to be an independent predictor of both 30-day (HR 1.57, 95% CI 1.45–1.70) and 365-day mortality (HR 1.48, 95% CI 1.40–1.56). K-M survival curve analyzes showed that patients with elevated GLR levels had worse survival outcomes than patients with lower levels. Furthermore, the predictive utility of GLR appeared to exceed that of glucose or lymphocyte counts alone. GLR may be a useful tool for early identification and treatment of high-risk populations in clinical practice and may also be a potential predictor of the prognosis of patients with heart failure.